1996
DOI: 10.1107/s0021889895015664
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition of KNO3 Monitored by Synchrotron X-ray Powder Diffraction

Abstract: The solid-state phase transitions of KNO3 were studied at atmospheric pressure in the temperature range 303 to 533 K by synchrotron X-ray powder diffraction. The detectors used were (i) a curved position-sensitive detector and (ii) a moving imaging-plate system built for time-, temperature-and wavelength-dependent powder diffraction. On heating, the transition from o~-KNO3 to /3-KNO3 occurs at 401 K. On cooling with a cooling rate of 7 K min -l, the transition from fl-KNO3 to "y-KNO3 was observed at 388 K. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 8 publications
1
26
2
1
Order By: Relevance
“…2, we observe that the stability of -KNO at 1253C increases as the sample is heat-cycled through the di!erent phases for a number of times. In this context we note that Christensen et al (2) observed the temperature interval for the appearance of -KNO to decrease on continuing cycling through the di!erent phases, i.e., from the range of 115}973C to the range of 115}1043C for 3 cycles. Also, we should point out that in our experiments we always observe -KNO along with the -KNO phase present in di!erent amounts.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…2, we observe that the stability of -KNO at 1253C increases as the sample is heat-cycled through the di!erent phases for a number of times. In this context we note that Christensen et al (2) observed the temperature interval for the appearance of -KNO to decrease on continuing cycling through the di!erent phases, i.e., from the range of 115}973C to the range of 115}1043C for 3 cycles. Also, we should point out that in our experiments we always observe -KNO along with the -KNO phase present in di!erent amounts.…”
Section: Resultsmentioning
confidence: 70%
“…A metastable phase of KNO has been observed by other methods upon cooling of -KNO . In particular, we note the recent synchrotron powder XRD study (2), which paid special attention to observing the -KNO phase by cooling -KNO . The spectral changes observed at 1253C upon cooling of the -KNO phase propose that the resonance appearing at 359.0 ppm arises from the metastable -KNO .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy-dispersive powder diffraction is well suited for time-resolved studies; however, monochromatic powder diffraction offers better d-space resolution, which is important in multi-phase studies. Monochromatic powder diffraction has been used successfully in a large number of studies using either conventional sources (see, for instance, Bdnard & Lou/Sr, 1995;Oyama, Hasegawa & Takei, 1994;Suda, Yashima, Kakihana & Yoshimura, 1994;Weber & Schweda, 1995) or synchrotron radiation (Pennartz, L6chner, Fuess & Wroblewski 1992: Christensen, Norby & Hanson, 1995Rizzo, Doyle & Wroblewski, 1995;Christensen, Norby, Hanson & Shimida, 1996). These studies have either employed conventional 0-20 scans or one-dimensional position-sensitive detectors.…”
Section: Introductionmentioning
confidence: 99%